An analysis of the development assistance for health (DAH) allocations for STD control in Africa - Fumitaka Furuoka; Mohammad Zahirul Hoque; Ray Ikechukwu Jacob; Patrick Ziegenhain (Cambridge University Press, 2019)
The Sustainable Development Goals set by the United Nations recognize the importance of making progress in the eradication and treatment of sexually transmitted deceases (STD). STD are among the most widespread diseases in the world and have the highest prevalence in Sub-Saharan Africa. The current study explored the associations between the allocation of the development assistance for health (DAH) in 54 African countries and key development indicators – STD incidence, Gross Domestic Product per capita, health expenditure, and life expectancy at birth. It employed descriptive statistical methods, the matrix scatter plot analysis and the Pearson correlation test for this purpose. The findings indicated that there was a considerable increase in the volume of the DAH given to control and prevent STD in Africa over the period of 2002–2011. A statistically significant positive association was detected between the STD incidence and the health aid allocations. At the same time, the imbalance in the distribution of the health aid between the major and minor aid recipients in the continent increased. The study concludes by discussing policy implications that can be drawn from these findings.